Tissue Expression of Prohibition-I and Its Relationship With Prognostic Factors in Breast Cancer - Hossein Javid; Isaac Hashemy; Soudabeh Shahid sales; Nema Mohammadian Roshan; Tayyebeh Kianoosh; Farnaz Zahedi Avval (Iranian Society of Pathology, 2018)
Background & objective: Globally, breast cancer is the most common malignancy among females. Prohibition (PHB)-I, a homologous protein, was initially introduced as a suppressor gene for amplification process. Further, the protein has a key role in the cell cycle and is capable of inhibiting DNA transcription in many cell types. Therefore, its possible role in different types of human malignancies is of interest. The current study aimed at examining the relationship between the tissue distribution of PHB-I and prognostic factors of breast cancer. Method: Paraffin-embedded tissue specimens of 33 patients diagnosed with breast cancer at Omid teaching Hospital, Mashhad, Iran were studied and a commercial monoclonal antibody was used to perform immunohistochemistry (IHC). The relationship between PHB-I tissue expression with age, disease stage, tumor grade and size, as well as hormone receptor status including estrogen (ER) and progesterone (PR) receptors, and Her-2 receptor were evaluated. Results: The Immunohistochemical analysis showed a relative increase in PHB-I tissue expression along with higher tumor grade (P=0.057). In addition, higher expression of ER and PR were observed (P=0.027 and 0.009, respectively). The age of patients and other prognostic factors including Her-2 receptor status and disease stage did not statistically correlate with PHB-I expression. Conclusion: An increased expression of PHB-I was observed in the breast cancer tumors of the current study patients compared with the anatomically healthy margin. Its coloration with some prognostic factors such as disease grade and expression of ER and PR might indicate the PHB-I potential application for diagnostic and patient management purposes.